Design and technological optimization of overhead traveling cranes’ box girders - Лятуринський, Василь Олександрович; Сидоренко, Михайло Володимирович (Technology audit and production reserves, 2015)
The residual stress-strain state of welded joints of cranes’ steel structures is understudied scientific and technical issue. Finite-element analysis of the post-weld residual stresses in longitudinal T-joints of overhead cranes’ box girders was applied to this study. Goldak’s moving heat source model based on double-ellipsoid heat flux distribution was used. Thermal and mechanical tasks were sequentially solved, wherein the phase transformation processes were taken into consideration. The effects of such factors as box girder geometry, welding speed, pre-heating technology on the residual stresses and phase distribution in longitudinal welds were further investigated. The post-weld stress-strain state of the box girders’ T-joints was detailed. The recommendations to streamline the overhead cranes girders’ production technology intended to improve their quality and overall technological level were formulated. The necessity of taking into account the phase and structural transformations in the simulation is proved. The requirements for the finite-element modeling of longitudinal T-joints were established.